THE SCHOOL AND THE TEACHER: CHANGES IN STUDENT PERCEPTION DURING THE PANDEMIC - Cristian BUCUR; Laura Elena CIOLAN; Anca PETRESCU (National Centre for Policy and Evaluation in Education, 2021)
The relationship between the learning environment and the learning behaviours has long been of interest in educational literature. When addressing the socioemotional stages, Erickson raises awareness of the psycho-social influence of school by way of diligence vs inferiority (Harwood et al., 2010), while Galos and Aldridge (2020) explore how designing a learning environment focused on student self-efficacy triggers statistically significant differences in 4 (out of 9) areas of analysis: fairness, task clarity, learning responsibility and task achievement. The aim of the present study is to highlight the significance and the differences in the main student psychosocial representations of school and teachers before and during the pandemic, the latter being characterised by government-imposed restrictions as well as changes in the student-teacher interaction, both during the second school term of 2019-2020 and the two school terms of the academic year 2020-2021. The areas we intend to explore are: overall attitude to school and student emotional states, the perception on teacher and peer relations, the perception on school as an organisation but also as a learning environment, the parents as a filter on schoolrelated perceptions, and the projective dimension on school life. The resulting statistical analysis (both nonparametric tests for independent groups and correlation) reveals major changes in the student perception on school and teachers, which will require systematic future intervention, as well as an upgrade of educational strategies, considering that the approaches designed and applied during the pandemic proved unable to compensate for the changes brought about by the restrictions on learning.